Silica Supported H3PW12O40: An Efficient Catalyst for the Synthesis of Spirooxindoles via a One-Pot Reaction under Solvent Free Conditions - Samadizadeh, Marjaneh (Asian Journal of Chemistry, 2012)
Silica supported tungstophosphoric acid was found to be an efficient catalyst for the solvent-free synthesis of spirooxindoles via a one-pot three component reaction of isatin, 1,3-cyclohexadione and 4-hydroxy-6-methyl-2H-pyran-2-one. This method has many advantages such as simple work-up, using reusable and heterogeneous catalyst and good yield.